2001
DOI: 10.1016/s1010-7940(01)00886-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lobectomy for lung cancer: a prospective study to compare patients with forced expiratory volume in 1 s more or less than 80% of predicted

Abstract: Lobectomy for cancer can be performed successfully also in selected patients with chronic obstructive pulmonary disease. Post-operative course and survival of these patients is not different from that of patients with normal FEV1, on the contrary, patients with low FEV1 may lose less pulmonary function or even mend it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 14 publications
3
26
0
5
Order By: Relevance
“…In patients with lung disease, careful evaluation of the type, degree and location of the lung abnormalities is important in order to select the best lung resection. This is particularly relevant in patients with emphysema of the upper lobes in whom a lobectomy will have a lung volume reduction effect, with improvement of postoperative lung function, whereas a segmentectomy would not achieve the same results [47]. Conversely, the preservation of lung function in patients with small lung cancers and anticipated long survival is important, considering the possibility of further lung resections to treat second primary lung tumours.…”
Section: Post-operative Pulmonary Functionmentioning
confidence: 99%
“…In patients with lung disease, careful evaluation of the type, degree and location of the lung abnormalities is important in order to select the best lung resection. This is particularly relevant in patients with emphysema of the upper lobes in whom a lobectomy will have a lung volume reduction effect, with improvement of postoperative lung function, whereas a segmentectomy would not achieve the same results [47]. Conversely, the preservation of lung function in patients with small lung cancers and anticipated long survival is important, considering the possibility of further lung resections to treat second primary lung tumours.…”
Section: Post-operative Pulmonary Functionmentioning
confidence: 99%
“…Many studies have shown the minimal loss or even the improvement in pulmonary function after lobectomy in COPD patients with cancer, questioning the traditional operability criteria mostly based on pulmonary parameters (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Pulmonary Function Evaluationmentioning
confidence: 99%
“…A growing number of studies in the recent years have reported an improvement of respiratory function after lobectomy in some patients affected by COPD [29], or at least a minimal impairment of respiratory function indicated by better apoFEV% (actual postoperative) than ppoFEV1% (predicted postoperative) [30]. In such cases Authors have hypothesized that lobectomy could have a lung volume reduction surgery (LVRS) effect [31].…”
Section: Lung Volume Reduction Era and Its Importance In Lung Cancer mentioning
confidence: 99%